PENGARUH PEMBERIAN PUDING DAUN KELOR TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DI KLINIK PERATAMA SEHATI HUSADA BIRU-BIRU TAHUN 2025 - Krisna, Putri; Musliah Sihaloho, Wilfa (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2026)
Low hemoglobin levels in pregnant women can lead to anemia. One way to increase hemoglobin levels is by consuming iron-rich foods, such as moringa leaf pudding. Moringa leaves contain iron, vitamin C, vitamin A, and antioxidants that are beneficial in increasing hemoglobin levels. The purpose of this study was to determine the effect of moringa leaf pudding on increasing hemoglobin levels in pregnant women. This research used a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 21 pregnant women selected using purposive sampling. The results showed that the average hemoglobin level before the intervention was 10.171 g/dl and increased to 11.281 g/dl after the intervention. Data were analyzed using the Paired Sample T-Test, which showed a significance value of p = 0.000 (< 0.05), indicating a significant effect of moringa leaf pudding on increasing hemoglobin levels in pregnant women. Conclusion: Moringa leaf pudding has a significant effect on increasing hemoglobin levels and can be used as a healthy food supplement alternative for pregnant women.